Geotechnical Evaluation of Subgrade Soil on the Frans Kasaipo Road in Tosa Urban Village - Idhar Adjam; Firman Anhar; Indra Altarans; Fitriyanti Faruk (SCIENTIA: Journal of Multi Disciplinary Science, 2026)
Soil is a vital natural resource that plays a crucial role in sustaining life. In addition to serving as a medium for plant growth, a provider of essential resources, and a physical foundation, soil also functions as an integral component of ecosystems. Degradation of soil functions may lead to ecosystem disturbances. The road section in Tosa Urban Village, East Tidore District, frequently experiences landslides during the rainy season. This road serves as a critical transportation route for the local community, supporting daily activities such as education, economic transactions, social interactions, and cultural events. Several segments of the road are characterized by steep slopes, which increase the potential for landslides, particularly during periods of high rainfall. Laboratory testing of soil samples from the Tosa area indicated a California Bearing Ratio (CBR) value of 5.77%, a maximum moisture content of 20.5%, and a maximum dry density of 1.73 g/cm³, reflecting very low bearing capacity. Grain size analysis showed that the natural soil consists predominantly of silt–clay materials, with more than 35% passing the No. 200 sieve, classifying it as A-7 soil according to the AASHTO system. The percentage passing the No. 200 sieve reached 108.77% for samples 1–3, exceeding the minimum classification requirement. The plasticity index was recorded at 14.91%. Atterberg limits testing further classified the soil as A-7-6, with a liquid limit exceeding 41% and a plasticity index greater than 11%. Specific gravity tests revealed that soil samples 1 and 2 are classified as humus soils, while sample 3 is identified as organic silt. Based on these findings, appropriate landslide mitigation measures for locations 1–3 include slope cutting, soil anchoring, and drainage system installation.